Environmental Management Accounting Practices for the Sustainable Development Change: A Case Study from a Sri Lankan Rubber Manufacturing Company - Navodya Sandamini; Kalani Dissanayake (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2022)
Every business has a responsibility beyond its basic responsibility to its shareholders. At present, people are more towards the environment, and accounting plays a crucial role by acting as a language of business. When referring to the environmental sensitive industries in Sri Lanka, the industrial processes connected to rubber manufacturing are harmful which can have negative environmental impacts. Accordingly, the discussion's critical part is based on the major environmental-related areas and their applicable environmental management practices. A qualitative approach was adopted in this study, occupying semi-structured interviews as the primary method of data collection. The study revealed a strict link between environment performance and the financial results of the case study organization. The study will provide businesses and managers the useful insights for implementing EMA practices and EMS applications as in the Sri Lankan context, well-established EMA related initiatives are rarely observable.